2014
DOI: 10.1128/mbio.01040-13
|View full text |Cite
|
Sign up to set email alerts
|

Live Attenuated Influenza Vaccine Enhances Colonization of Streptococcus pneumoniae and Staphylococcus aureus in Mice

Abstract: Community interactions at mucosal surfaces between viruses, like influenza virus, and respiratory bacterial pathogens are important contributors toward pathogenesis of bacterial disease. What has not been considered is the natural extension of these interactions to live attenuated immunizations, and in particular, live attenuated influenza vaccines (LAIVs). Using a mouse-adapted LAIV against influenza A (H3N2) virus carrying the same mutations as the human FluMist vaccine, we find that LAIV vaccination reverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
90
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(104 citation statements)
references
References 50 publications
10
90
0
3
Order By: Relevance
“…Placebo-controlled <5 50.9% (not included) Turkey [101] Placebo-controlled (pooled data) <7 10.9% (1.3-19.7) Multinational [105] IIV-controlled (pooled data) <6 9.1% (-0.7-17.9) Multinational [105] Case-control 17-35 0.34 (0.29-0.40) ‡ USA looked at the bacterial load in the respiratory tract [110]. Remarkably, they showed that after vaccination with LAIV, there was an increase in bacterial density and duration of colonization in the upper respiratory tract, and this for up to 4 weeks after vaccination.…”
Section: Pneumococcal Vaccine Studies Measuring Protection Against Inmentioning
confidence: 99%
“…Placebo-controlled <5 50.9% (not included) Turkey [101] Placebo-controlled (pooled data) <7 10.9% (1.3-19.7) Multinational [105] IIV-controlled (pooled data) <6 9.1% (-0.7-17.9) Multinational [105] Case-control 17-35 0.34 (0.29-0.40) ‡ USA looked at the bacterial load in the respiratory tract [110]. Remarkably, they showed that after vaccination with LAIV, there was an increase in bacterial density and duration of colonization in the upper respiratory tract, and this for up to 4 weeks after vaccination.…”
Section: Pneumococcal Vaccine Studies Measuring Protection Against Inmentioning
confidence: 99%
“…Emigration of oral microbes to the lower airways due to aspiration is important in a number of respiratory conditions, in which a large fraction of infections are believed to have oral microbial etiology (35)(36)(37)(38)(39). Respiratory conditions associated with decreased extinction of microbes that reach the lower airways include smoking (31), vaccination and probiotics (40,41), respiratory virus infection (42)(43)(44), pneumonia (36), HIV (45,46), COPD (30,(47)(48)(49), and CF (50). In addition, improvements in oral hygiene practices in hospitals have been shown to prevent pneumonia (51).…”
Section: A Bridge To the Lung: Migration Across The Tracheamentioning
confidence: 99%
“…It is reported that vaccine-induced immunity to influenza virus can limit the mortality rate caused by secondary pneumococcal infection after influenza (17). While vaccinating mice with live attenuated influenza vaccine (LAIV) can reduce pneumococcal carriage after influenza virus infection (18), receiving LAIV can, on the other hand, enhance pneumococcal colonization in the absence of influenza virus infection (19). Previous studies highlighted the complexity of the interaction between LAIV and pneumococcal carriage and suggested the importance of anti-influenza virus antibody to control the dual attack by influenza virus and pneumococcus.…”
mentioning
confidence: 99%